2006
DOI: 10.1002/nau.20352
|View full text |Cite
|
Sign up to set email alerts
|

A statistical comparison of pad numbers versus pad weights in the quantification of urinary incontinence

Abstract: Aims: Pad per day (PPD) usage is a frequently utilized measure of urinary incontinence. The 24-hour pad weight test (24PWT) is a reproducible test for quantifying incontinence volumes. We investigated whether PPD validly reports the magnitude of urinary incontinence. Methods: This was a retrospective review of patients undergoing stress incontinence surgery from July 2002 to 2005. Inclusion criteria were a documented 24PWT and patient-reported PPD usage. Grams of urine loss per pad (GPP) provided a third measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 11 publications
5
61
1
Order By: Relevance
“…Eastham et al 10 reported that resection of one or both bundles substantially decreases the continence rate, but this factor continues to be widely debated. 11 We chose the 24 hr Pad test because it is a useful way to quantify incontinence, superior than Pad per day usage, which is an unreliable measure of incontinence only measuring 38% of the variation of urinary incontinence volume 12 and than 1 hr Pad test which is not so sensitive in the detection of slight leakages. 13 The majority of incontinent patients complained of urine leakage during the second half of the day, commonly moving into sitting or standing.…”
Section: Demonstrated Beneficial Effects Ofmentioning
confidence: 99%
“…Eastham et al 10 reported that resection of one or both bundles substantially decreases the continence rate, but this factor continues to be widely debated. 11 We chose the 24 hr Pad test because it is a useful way to quantify incontinence, superior than Pad per day usage, which is an unreliable measure of incontinence only measuring 38% of the variation of urinary incontinence volume 12 and than 1 hr Pad test which is not so sensitive in the detection of slight leakages. 13 The majority of incontinent patients complained of urine leakage during the second half of the day, commonly moving into sitting or standing.…”
Section: Demonstrated Beneficial Effects Ofmentioning
confidence: 99%
“…Dylewski et al [10] also showed that the correlation of grams urine loss per day versus actual pads per day is poor. Moreover, Wallerstedt et al [11] demonstrated that patients using only a safety pad had 5 times higher risk of bother than those using no pads after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Larger differences occurred in patients who suffered from moderate PSUI (12.1 vs. 25.9 %). Pads usage is a simple tool routinely used in the clinical practice, but its objective measurement of PSUI severity might be limited by differences of patients' daily physical activity [24,25]. In addition, PSUI severity was assessed by 1-h pad test.…”
Section: Discussionmentioning
confidence: 99%